Diversity Of Mangrove Plants In Balikpapan Bay and Mahakam Delta, East Kalimantan Province - Haydar, Muhammad Hijri; Atmoko, Tri; Indonesia (Berkala Ilmiah Biologi, 2025)
Mangroves provide many benefits for the environment and humans. Overexploitation will damage mangrove plants so that it will reduce the benefits of mangroves. Mangrove plant inventory can provide information on the diversity and composition of mangroves in Balikpapan Bay and Mahakam Delta as a database for mangrove monitoring. This study was conducted to study the diversity and comparison of mangrove plant composition in Balikpapan Bay and Mahakam Delta, East Kalimantan. Sampling is carried out by tracing the waterway with the purposive sampling method. The samples were dried into dried herbarium specimens and identified at the Plant Systematics Laboratory, Faculty of Biology UGM. The identification work was completed with descriptions and artificial identification keys then continued with a comparative analysis of the composition using the Sorensen Similarity Index. The results of research conducted showed that there are 44 species belonging to 15 orders, 25 families, and 35 genera. Balikpapan Bay shows higher mangrove diversity, with 32 species, compared to Mahakam Delta, with 24 species. The most common genera are Avicennia, Bruguiera, Ceriops, Rhizophora, Sonneratia, and Xylocarpus. The species composition of mangroves between Mahakam Delta and Balikpapan Bay shows a low level of similarity, with a similarity value of 40.67%.